PERANAN UNIT TIPIDTER (TINDAK PIDANA TERTENTU) DALAM MENCEGAH TERJADINYA TINDAK PIDANA PERTAMBANGAN TANPA IZIN DI WILAYAH HUKUM POLDA SUMATERA BARAT - Failin Failin; Anny Yuserlina (Ensiklopedia of Journal, 2023)
One of the tough challenges faced by countries rich in natural resources is the rise of illegal or unlicensed mining. This is because mining not only harms the country financially, but often causes various problems such as environmental damage, social conflict, economic inequality or even encourages new poverty. For this reason, Article 2 of Law Number 4 of 2009 concerning Mineral and Coal Mining, determines the legal principles of Mineral and Coal Mining namely, the principle of benefit, the principle of justice, the principle of balance, the principle of partiality to the interests of the nation, the principle of participation, the principle of transparency, the principle of accountability, sustainability and environmental awareness. Based on the above principles, there is a balance principle, the principle of balance is a principle which requires that in the implementation of Mineral and Coal Mining a position of rights and obligations must be equal and balanced between the licensor and the permit holder. Keywords:  Role, Tipidter Unit, Prevention, Crime, Mining, Without a Permit